Challenges and opportunities in artisanal fisheries (Sonadia Island, Bangladesh): The role of legislative, policy and institutional frameworks. (15th February 2021) - Alam, Shawkat; Rahman, Mizanur; Al Arif, Abdullah
Graphical abstract: Image 1 Highlights: Role of legal and institutional framework of Bangladesh for conserving artisanal fisheries and marine resources. Policy interventions will be essential to ensure that artisanal fishers are able to understand and exercise their rights. Holistic approach needed to incorporate the principle of sustainable management into the current marine fisheries framework. Underlying socio-economic conditions that inhibit the artisanal fishers from having secure livelihoods need addressing.